Addiction‐Specific CACREP Standards in Clinical Mental Health Counseling Programs: How Are They Met?. Issue 2 (10th October 2013) - Iarussi, Melanie M.; Perjessy, Caroline C.; Reed, Shelley W.
<x xml:space="preserve">Abstract</x> In 2009, the Council for Accreditation of Counseling and Related Educational Programs (CACREP) included training standards specific to addiction for clinical mental health counseling programs. This study surveyed CACREP‐accredited program coordinators to determine how addiction‐specific standards were addressed.